Preliminary study on waste management for implementation of green highway / Asmalia Che Ahmad ... [et al.] - Asmalia, Che Ahmad; Nur Illiana, Husin; Abdul Muhaimin, Ab Wahid; Syahrul Nizam, Kamaruzzaman (2015)
Green highway is the transportation corridors which based on relatively new concept of roadway design. It incorporates both transportation functionality and ecological requirements. Green highway also provide more sustainable construction technique that maximize the lifespan of highway. Waste management is one of the importance criteria in the elements of green highway. This is because, management of construction waste is becoming a pressing problem worldwide. There is a need to reduce the amount of waste production, reduce the cost for managing the waste as well as saving the environment. This paper aims to identify the criteria of waste management in development of green highway. This is exploratory study focus only on green highway. Preliminary study was done using quantitative method. 30 sets of questionnaires have been distributed to highway construction experts. The data was analyzed using Statistical Packages for Social Science (SPSS). The results from the analysis shows wood is the highest production of waste and reused back the material is the best way to minimize the waste.